Two Replication Studies of a Time-Reversed (Psi) Priming Task and the Role of Expectancy in Reaction Times - Schlitz, Marilyn; Bem, Daryl; Marcusson-Clavertz, David; Cardena, Etzel; Lyke, Jennifer; Grover, Raman; Blackmore, Susan; Tressoldi, Patrizio; Roney-Dougal, Serena; Bierman, Dick; et al. (Journal of Scientific Exploration, 2021)
Two experiments involving an international collaboration of experimenters sought to replicate and extend a previously published psi experiment on precognition by Daryl Bem that has been the focus of extensive research. The experiment reverses the usual cause–effect sequence of a standard psychology experiment using priming and reaction times. The preregistered confirmatory hypothesis is that response times to incongruent stimuli will be longer than response times to congruent stimuli even though the prime has not yet appeared when the participant records their judgments. The confirmatory hypothesis for Experiment 1 was not supported. Exploratory analyses indicated that those participants who completed the English-language version rather than a translation showed a significant effect, as was the case in the original study; no significant departure from chance was found in data involving non-English translations. Experiment 2 sought to enhance the predicted effect by having each participant read either a pro-psi or an anti-psi statement at the beginning of the experiment to test the pre-recorded hypothesis that a pro-psi statement would produce a larger effect than an anti-psi statement. The results did not support the primary psi hypothesis and there was no effect in the English-language sample. However, there was mixed support for the effect of the psi statement on performance; those participants who received the pro-psi statement had a greater psi score than those who received the anti-psi statement. As in the original experiment, neither the experimenters’ nor participants’ beliefs were significantly associated with the dependent measure. In sum, the pre-registered confirmatory hypotheses were not supported. The importance of the personality variable Sensation Seeking, a component of extraversion, as a correlate of psi performance is discussed as are the challenges and implications for international collaborations and replication in controversial science. Keywords: priming; expectancy effect; retrocausation; consciousness; sociology; precognition; psi; replication Two experiments involving an international collaboration of experimenters sought to replicate and extend a previously published psi experiment on precognition by Daryl Bem that has been the focus of extensive research. The experiment reverses the usual cause-effect sequence of a standard psychology experiment using priming and reaction times. The preregistered confirmatory hypothesis is that response times to incongruent stimuli will be longer than response times to congruent stimuli even though the prime has not yet appeared when the participant records his or her judgments. The confirmatory hypothesis for Study 1 was not supported. Exploratory analyses indicated that those participants who completed the English-language version rather than a translation showed a significant effect, as was the case in the original study; no significant departure from chance was found in data involving non-English translations. Study 2 sought to enhance the predicted effect by having each participant read either a pro-psi or an anti-psi statement at the beginning of the experiment to test the pre-recorded hypothesis that a pro-psi statement would produce a larger effect than an anti-psi statement. The results did not support the primary psi hypothesis and there was no observed association between belief and experience of ESP and psi outcome. However, there was mixed support for the effect of the psi statement on performance; those participants who received the pro-psi statement had a greater psi score than those who received anti-psi statement. As in the original experiment, neither the experimenters’ nor participants’ beliefs or expectations were significantly correlated with the dependent measure. In sum, the pre-registered confirmatory hypotheses were not supported. The importance of the personality variable Sensation Seeking, a component of extraversion, as a correlate of psi performance is discussed as are the challenges and implications for international collaborations and replication in controversial science.